2022
DOI: 10.48550/arxiv.2204.04746
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CholecTriplet2021: A benchmark challenge for surgical action triplet recognition

Abstract: Context-aware decision support in the operating room can foster surgical safety and efficiency by leveraging real-time feedback from surgical workflow analysis. Most existing works recognize surgical activities at a coarse-grained level, such as phases, steps or events, leaving out fine-grained interaction details about the surgical activity; yet those are needed for more helpful AI assistance in the operating room. Recognizing surgical actions as triplets of instrument, verb, target combination delivers compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 49 publications
(88 reference statements)
0
9
0
Order By: Relevance
“…Of these teams, a total of 11 teams progressed beyond the validation phase; as detailed in Fig 2, these teams were drawn from 9 different countries and 3 continents. This final participation was just over half of the CholecTriplet 2021 challenge (Nwoye et al, 2022a); we also observed a drop in the relative ratio between the final participants and total registrants (45.5% in 2021; 34.4% in 2022). We identified 2 likely reasons for the drop in each of these statistics:…”
Section: Participation Statisticsmentioning
confidence: 70%
See 4 more Smart Citations
“…Of these teams, a total of 11 teams progressed beyond the validation phase; as detailed in Fig 2, these teams were drawn from 9 different countries and 3 continents. This final participation was just over half of the CholecTriplet 2021 challenge (Nwoye et al, 2022a); we also observed a drop in the relative ratio between the final participants and total registrants (45.5% in 2021; 34.4% in 2022). We identified 2 likely reasons for the drop in each of these statistics:…”
Section: Participation Statisticsmentioning
confidence: 70%
“…In 2021, we introduce the first endoscopic vision challenge focusing on the recognition of surgical activities in the form of triplets (Nwoye et al, 2022a). A rerun of this challenge in the current edition is with two notable advances: (1) the increment of the task difficulty from presence to spatial detection, which also increases the task usefulness, and (2) the addition of spatial bounding box labels to challenge evaluation data thereby enriching the dataset.…”
Section: Benchmark Challenge: From Recognition To Detectionmentioning
confidence: 99%
See 3 more Smart Citations